2015
DOI: 10.1192/bjp.bp.114.148551
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for post-traumatic stress disorder: Systematic review and meta-analysis

Abstract: Some drugs have a small positive impact on PTSD symptoms and are acceptable. Fluoxetine, paroxetine and venlafaxine may be considered as potential treatments for the disorder. For most drugs there is inadequate evidence regarding efficacy for PTSD, pointing to the need for more research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
164
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 326 publications
(196 citation statements)
references
References 68 publications
7
164
1
5
Order By: Relevance
“…It is important to note that medication effects are lower than those observed in the psychological intervention [27]. Nevertheless, good evidence of ef icacy has been produced by some medications, such as paroxetine, venlafaxine, and luoxetine, at the same time most drugs lack proper proof of their ef icacy for PTSD [27]. By contrast, in one of the studies conducted by Lee et al (2016), the results indicated the small positive effect of paroxetine and luoxetine, while sertraline, venlafaxine, and nefazodone outperformed other medications [28].…”
Section: Pharmacological Interventionsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is important to note that medication effects are lower than those observed in the psychological intervention [27]. Nevertheless, good evidence of ef icacy has been produced by some medications, such as paroxetine, venlafaxine, and luoxetine, at the same time most drugs lack proper proof of their ef icacy for PTSD [27]. By contrast, in one of the studies conducted by Lee et al (2016), the results indicated the small positive effect of paroxetine and luoxetine, while sertraline, venlafaxine, and nefazodone outperformed other medications [28].…”
Section: Pharmacological Interventionsmentioning
confidence: 97%
“…It is important to note that medication effects are lower than those observed in the psychological intervention [27]. Nevertheless, good evidence of ef icacy has been produced by some medications, such as paroxetine, venlafaxine, and luoxetine, at the same time most drugs lack proper proof of their ef icacy for PTSD [27].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Once and again, in the pharmacological domain, meta-analysis has shown that there is no single elective medication for a definite DSM-V disorder (such as PTSD) in spite of what the pharmaceutical industry tries to demonstrate. 44,45 Imitating pharmacological research in the domain of psychotherapy or counselling by using strict manualized procedures as if they were pills implies four erroneous assumptions are made:…”
Section: And Then Came the Manualsmentioning
confidence: 99%
“…PTSD is tenacious, debilitating, and treatment refractory in many cases (Breslau, Peterson, Poisson, Schultz, & Lucia, 2004; Hoskins et al, 2015; Institute of Medicine, 2014; Kessler, 2000; Roberts, Roberts, Jones, & Bisson, 2015, 2016; Schnyder et al, 2015; Sijbrandij, Kleiboer, Bisson, Barbui, & Cuijpers, 2015). Early interventions may reduce the prevalence of chronic PTSD among survivors at risk (Kearns, Ressler, Zatzick, & Rothbaum, 2012), but they are resource demanding and effective in only a subset of survivors.…”
Section: Introductionmentioning
confidence: 99%